Ideas: Jane Goodall: “We’ve sent a rocket up to Mars, yet we’re not intelligent” - United Nations Educational, Scientific; Cultural Organization; Jane Goodall (The UNESCO Courier, 2025)
Globally renowned British ethologist and anthropologist, Dr Jane Goodall is known for her pioneering research into the relationship between humans and animals, chimpanzees in particular. The influential environmental activist spoke at UNESCO Headquarters in Paris on 19 October 2024. Below are excerpts from her speech, in which she talks about her long fight to preserve wild animal life while conveying a message of peace and hope.